O efeito do desenvolvimento financeiro na desigualdade de renda nos municípios do Ceará - Paula, Antonia Leda Morais de (2015)
This work seeks to investigate an eventual relationship between financial development and income inequality. For this, was used data from 184 cities from Ceará, at the year of 2010, Using as a measure of inequality, the Gini index and, as explanatory variables, the reasons established between credit and GDP, between credit and GDP operations; between credit and population operations; between financing and GDP and, finally, between funding and population, as proxies for financial development. Was used the method called Jackknife Model Averaging, which is characterized by being a procedure of estimation that takes into account all possible model specifications based on a set of variables. We used also the FMA approach suggested in Hansen and Racine (2012). The results indicate that financial development is not statistically relevant to interfere in reducing income inequality.